The Effect of Employee Digital Competencies, Technology Infrastructure, and Local Government Support on the Effectiveness of Islamic Banking Digitalization in Bandung City (West Science Interdisciplinary Studies, 2025)
This study investigates the factors influencing the effectiveness of Islamic banking digitalization in Bandung City. Specifically, it examines the roles of Employee Digital Competencies (EDC), Technology Infrastructure (TEI), and Local Government Support (LGS) in shaping the success of digital transformation in Islamic banking institutions. A total of 220 respondents from various Islamic banks in Bandung participated in this research. Data were collected through a structured questionnaire with a 5-point Likert scale, and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results reveal that Employee Digital Competencies, Local Government Support, and Technology Infrastructure significantly and positively influence the effectiveness of digitalization. The findings suggest that employee skills, government support, and robust technology infrastructure are essential for successful digital transformation in Islamic banking. This study contributes to the understanding of the digitalization process in Islamic financial services and provides practical recommendations for banking practitioners and policymakers in fostering an environment conducive to digital innovation.